2012
DOI: 10.1111/j.1469-7610.2012.02569.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled double‐blind trial of optimal dose methylphenidate in children and adolescents with severe attention deficit hyperactivity disorder and intellectual disability

Abstract: Optimal dosing of methylphenidate is practical and effective in some children with hyperkinetic disorder and intellectual disability. Adverse effects typical of methylphenidate were seen and medication use may require close monitoring in this vulnerable group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
65
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(68 citation statements)
references
References 25 publications
0
65
0
3
Order By: Relevance
“…For example, work from the National Survey of Children’s Health found that approximately 20% of nearly 1,500 children aged 2–17 with parent-reported ASD were initially given a diagnosis of ADHD, and were diagnosed with ASD three years later than children without ADHD concerns (Miodovnik et al 2015). Studies also indicate differences in response to treatments based on presence/absence of ADHD symptoms in children with ASD (Antshel et al 2011; Cortese et al 2012; Pearson et al 2012; Simonoff et al 2013). Finally, concerns about attention problems, in both those with ASD and their siblings, that persist into middle childhood and school settings also underscore the importance of developing a better understanding of how the two disorders manifest alone and together in childhood (Miller et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For example, work from the National Survey of Children’s Health found that approximately 20% of nearly 1,500 children aged 2–17 with parent-reported ASD were initially given a diagnosis of ADHD, and were diagnosed with ASD three years later than children without ADHD concerns (Miodovnik et al 2015). Studies also indicate differences in response to treatments based on presence/absence of ADHD symptoms in children with ASD (Antshel et al 2011; Cortese et al 2012; Pearson et al 2012; Simonoff et al 2013). Finally, concerns about attention problems, in both those with ASD and their siblings, that persist into middle childhood and school settings also underscore the importance of developing a better understanding of how the two disorders manifest alone and together in childhood (Miller et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Dose titration in the MPH treatment is recommended for optimal response and minimum adverse effects. 6 However, there are limited studies investigating the relationship between OROS-MPH doses and plasma MPH concentrations in children and adolescents. A small study (n = 17) reported that high-dose OROS-MPH, used with other medications, was not associated with unusually elevated plasma MPH concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies have shown severe adverse effects with methylphenidate including social withdrawal, irritability, insomnia, and anorexia in children with ASD [34].…”
Section: Stimulants and Non-stimulantsmentioning
confidence: 99%